Tax Audit and its Effect on Tax Compliance of MSMEs in Nigeria - Ellawule, Abdulhamid; Bashir, Yusuf Maiwada; Dalhat, Bala Sulaiman; Suleiman, Naziru (The Journal of Accounting and Management, 2024)
The self-assessment regime comes with a lot of challenges in the tax system. One of the problems is tax compliance problem. This study, therefore, investigated the effect tax audits have on tax compliance of MSMEs in Nigeria. 500 MSMEs were selected for the study and the regression method through Statistical Package for Social Sciences (SPSS) was used for the analysis. The study found that tax audits do have a significant effect on the tax compliance of MSMEs in Nigeria. Also, intentional tax fraud investigation and enterprise tax return verification both have a significant effect on the tax compliance of MSMEs in Nigeria. Most of the local government revenue collectors or their agents have little or no adequate technical know-how to carry out tax audits on the businesses when the integrity of the books of account of the businesses is in doubt. To improve the tax base of the country, the government should train and retrain the tax authority staff and their agents to enhance their capacities in carrying out their assignment of collecting revenue and tax audits when the need arises.